The effect of different vineyard management systems on the epigaeic arthropod assemblages in the Cape Floristic Region, South Africa - Gaigher, Rene (Stellenbosch : Stellenbosch University, 2008)
Thesis (MScConsEcol (Conservation Ecology and Entomology)--Stellenbosch University, 2008.